Model development and small‐signal stability analysis of DFIG with stator winding inter‐turn fault. Issue 3 (27th January 2017) - Sun, Liling; Xu, Boqiang; Du, Wenjuan; Wang, Haifeng
Abstract : Much attention has been continuously paid on the model development and stability analysis of the doubly fed induction generator (DFIG) widely applied in wind power generation. Similarly, this study develops the form‐standardised state‐space model in the dq reference frame of the DFIG with stator winding inter‐turn fault (SWITF). Compared with those previously developed, it is definitely preferable for the simulation and stability analysis of the DFIG with SWITF due to its standard form. Moreover, for the DFIG with SWITF working in stator‐voltage‐oriented control frame, the small‐signal stability analysis is conducted using MATLAB simulation, yielding the conclusion that SWITF will never eradicate the DFIG's small‐signal stability but deteriorate it to some extent. This conclusion is further validated by means of the Lyapunov stability theory. As a kind of contribution of this study, the analytical expressions of the eigenvalues of the DFIG with SWITF are derived. Case study based on an MATLAB/Simulink demo routine is completed to demonstrate the validity of the model development and small‐signal stability analysis of the DFIG with SWITF.